Letter (copy) : International Solidarity Fund - Tewson, Vincent
032-0089-001 9020 — 9434. 3rd March, 1939. Our Ref: HVT/FC/347. Mr. D. C. Norris, 14, City Road, Finsbury Square, E.C.1. Dear Mr. Norris, INTERNATIONAL SOLIDARITY FUND. Many thanks for your letter of 1st March enclosing cheque for £2.2.0d., our official receipt for which is enclosed herewith. I should like to say how greatly we appreciate your help. In regard to the point you raise the demands upon the Fund will be as great as ever. Not only are we confronted with a refugee problem, but we must continue to send food to Central Spain. For some time we have had two Committees working - one which was in Barcelona has now moved in to France and is attempting to alleviate the lot of the Spanish refugees there and the other remains in Central Spain continuing with the work. We do not anticipate any great difficulty in getting food into Central Spain providing funds are forthcoming. The whole position is more appalling than ever, and the greater our need the more we appreciate the constant help which is being given by our friends. Yours sincerely, for Joint Secretary. Receipt. 292/946/32/89